Biogas production coupled to repeat microalgae cultivation using a closed nutrient loop. (September 2018) - González-González, Lina María; Zhou, Lihong; Astals, Sergi; Thomas-Hall, Skye R.; Eltanahy, Eladl; Pratt, Steven; Jensen, Paul D.; Schenk, Peer M.
Graphical abstract: Highlights: A closed nutrient loop for microalgal biogas and biomass production was developed. Up to 199 mL methane g −1 VS was achieved without any pre-treatment of algal feed. Nutrient-rich digestate was effectively recycled for repeat algal biomass production. 36× dilution of liquid digestate achieved best results, superior to inorganic medium. Abstract: Anaerobic digestion is an established technology to produce renewable energy as methane-rich biogas for which microalgae are a suitable substrate. Besides biogas production, anaerobic digestion of microalgae generates an effluent rich in nutrients, so-called digestate, that can be used as a growth medium for microalgal cultures, with the potential for a closed nutrient loop and sustainable bioenergy facility. In this study, the methane potential and nutrient mobilization of the microalga Scenedemus dimorphus was evaluated under continuous conditions. The suitability of using the digestate as culture medium was also evaluated. The results show that S. dimorphus is a suitable substrate for anaerobic digestion with an average methane yield of 199 mL g −1 VS. The low level of phosphorus in digestate did not limit algae growth when used as culture medium. The potential of liquid digestate as a superior culture medium rather than inorganic medium was demonstrated.